THE ABUNDENCES OF NUCLIDES MAGNESIUM IN THE ATMOSPHERES OF ARCTURUS AND ALDEBARAN - Gorbanjeva, T. I.; Kantzen, L. E.; Komarov, N. S. (Одеські астрономічні публікації, 2017)
The abundances of nuclides magnesium in the atmospheres of Arcturus and Aldebaran thick and thin disks of Galaxy have been studied. The stars have various chromospheric activity. We used the new data on molecular constants of radiation for every electrically-vibrationally-rotating line of molecular system A2 Π-X2 Σ for MgH. The synthetic spectra were calculated. The values determined are generally close, but not equal, to the solar ratios.